If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -86 = -7n + 4(-1n + -5) Reorder the terms: -86 = -7n + 4(-5 + -1n) -86 = -7n + (-5 * 4 + -1n * 4) -86 = -7n + (-20 + -4n) Reorder the terms: -86 = -20 + -7n + -4n Combine like terms: -7n + -4n = -11n -86 = -20 + -11n Solving -86 = -20 + -11n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '11n' to each side of the equation. -86 + 11n = -20 + -11n + 11n Combine like terms: -11n + 11n = 0 -86 + 11n = -20 + 0 -86 + 11n = -20 Add '86' to each side of the equation. -86 + 86 + 11n = -20 + 86 Combine like terms: -86 + 86 = 0 0 + 11n = -20 + 86 11n = -20 + 86 Combine like terms: -20 + 86 = 66 11n = 66 Divide each side by '11'. n = 6 Simplifying n = 6
| 7-3x-5-3x=5 | | Kx-3x=-2+5k | | 360-76= | | -8-14v=314 | | 5(-x-3)=5 | | 16x+34x+24x=370 | | 9(n+12)=144 | | 180-76= | | -3(x-7)=2(3x-5) | | 28=2+2a | | 2(x-8)-5(x+6)=2 | | -3x+21=6x-10 | | 4a-3b+2c= | | 100=4r | | M+(-19)=40 | | 6x+6=9x-6 | | (ab+4a+-6)+(ab+6)= | | 7(b+2)-13b=2(b-1)+6 | | 585.00+0.13x=525.00+0.21x | | x^2-2x+y^2-2y-3=0 | | X^3+7x-x-7=0 | | 2x-6=2(2-8)+10 | | 2x+6=y+4 | | 2x^2+-4x=0 | | 525.00+0.21x=585 | | 3x-2(5y-6)=8 | | 10(z+3)=5(z-8) | | 5-(x+3)=10 | | -t+15=2 | | 3u+147=180 | | x(x+1)=1024 | | x=15+7x-81 |